2021
DOI: 10.1016/j.bioactmat.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance evaluation of additively manufactured composite lattice structures of commercially pure Ti (CP–Ti)

Abstract: Ti alloys with lattice structures are garnering more and more attention in the field of bone repair or regeneration due to their superior structural, mechanical, and biological properties. In this study, six types of composite lattice structures with different strut radius that consist of simple cubic (structure A), body-centered cubic (structure B), and edge-centered cubic (structure C) unit cells are designed. The designed structures are firstly simulated and analysed by the finite element (FE) method. Comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Their results demonstrated that the optimized honeycomb structures had much lower stress and deformation. Xu et al (2021) investigated six composite lattice structures with different support radii consisting of simple cubic, body-centered cubic (BCC), and edge-centered cubic cells. Luxner et al (2007) and Han et al (2017) also suggested that BCC structures can have relatively higher porosity controllability and better mechanical properties than other structures.…”
Section: Introductionmentioning
confidence: 99%
“…Their results demonstrated that the optimized honeycomb structures had much lower stress and deformation. Xu et al (2021) investigated six composite lattice structures with different support radii consisting of simple cubic, body-centered cubic (BCC), and edge-centered cubic cells. Luxner et al (2007) and Han et al (2017) also suggested that BCC structures can have relatively higher porosity controllability and better mechanical properties than other structures.…”
Section: Introductionmentioning
confidence: 99%
“…FEA is commonly used for simulating the experimental process and validating testing results. Researchers usually conducted FEA for performance evaluation [50][51][52], structure design [53], investigating configurational effects [54], and studying the failure mechanism [55,56]. Digital image correlation (DIC) is a 3D, full-field, non-contact optical technique to measure contour, deformation, vibration, and strain on almost any material.…”
Section: Introductionmentioning
confidence: 99%
“…The relative density of the samples was determined in accordance with the ASTM B962‐14 standard. [ 17,18 ] The characterization process involved the following steps: first, the sample was put in a closed container and vacuum for about 30 min to reach a certain degree of vacuum. Then, inject water into the closed container and continue to vacuum for another 30 min.…”
Section: Methodsmentioning
confidence: 99%